When small-sized and non-innovating firms meet a crisis: Evidence from the Italian labour market - Perri, Stefano (2018)
The Italian jobs crisis consists of a high percentage of non-working labour force, matched with a high percentage of discouraged, long-term unemployed and inactive population. Not only a sharp deregulation of the job market is groundless, but even a hypothetic return to expansionary fiscal policy would be insufficient in order to solve such structural problems. Starting from the literature dealing with the "Italian decline", this article demonstrates that the current problems of the Italian labour market are strictly connected to both (post-crisis) fiscal adjustment and pre-existing features of the industrial branch.